2010
DOI: 10.1159/000320268
|View full text |Cite
|
Sign up to set email alerts
|

Determination of <i>Francisella tularensis</i> AcpB Acid Phosphatase Substrate Preferences

Abstract: The Francisella speciesencode 4 main acid phosphatases (Acp) that are potentially involved in pathogenesis through currently unknown mechanisms. Only 2 of these enzymes, AcpA and AcpC, have been biochemically characterized to date. In this work we describe the catalytic properties of Francisella tularensis AcpB utilizing an array of 120 phosphorylated substrates. In contrast to most acid phosphatases, the purified enzyme showed a narrow range of substrate preferences, with the highest affinity towards thiamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In a subsequent enzymatic assay, LotP's activity towards several nucleosides was tested in parallel. Malachite green was used to detect the P i released by the enzyme action (Crowe et al ., ). The results demonstrated that LotP preferentially used ATP as an enzyme substrate (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a subsequent enzymatic assay, LotP's activity towards several nucleosides was tested in parallel. Malachite green was used to detect the P i released by the enzyme action (Crowe et al ., ). The results demonstrated that LotP preferentially used ATP as an enzyme substrate (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…B. Steady‐state kinetic characterization of ATP ase activity. Initial rates of the reactions were determined at fixed concentrations of ATP , and the P i released was quantified by using Malachite green reagent as previously described (Crowe et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation